Monte Walsh [videorecording (DVD)] : a real western - Fraker, William A., 1923-2010; Barry, John, 1933-2011; Marvin, Lee; Palance, Jack, 1919-2006; Moreau, Jeanne, 1928-2017; Schaefer, Jack, 1907-1991 (Paramount Home Entertainment, 2010)
"Facing a changing landscape where barbed wire and railways replace the freedom of the open range, Monte Walsh (Marvin) and his fellow cowboys consider new work opportunities, toy with the idea of 'settling down', and draw their pistols for one last showdown."--Container.